Effect of plant growth regulators on growth and flowering of calendula (Calendula officinalis L.) under Malwa plateau of M.P. - PATIDAR, KAVITA; ANUJ KUMAR; KANWAR, JYOTI; SINGH, O.P.; PATIDAR, MANAK (Journal of Ornamental Horticulture, 2024)
The present investigation entitled "Effect of Plant Growth Regulators on Growth and Flowering of Calendula (Calendula officinalis L.) under Malwa Plateau of M.P." was conducted during Rabi 2020-2021 at the Experimental Field, Department of Floriculture and Landscape Architecture, K.N.K. College of Horticulture, Mandsaur (M.P.). The experiment was laid out in a randomized block design with three replications and used different plant growth regulators viz. T1 (Control), T2 (GA3 @ 250 ppm), T3 (GA3 @ 300 ppm), T4 (GA3 @ 350 ppm), T5 (NAA @ 150 ppm), T6 (NAA @ 200 ppm) and T7 (NAA @ 250 ppm). The result revealed that T4 (GA3 @ 350 ppm) proved better than all other treatments with respect of various attributes such as plant height (cm), number of leaves, number of branches / plant, maximum number of flowers/ plant, number of flowers each stem and flowering duration (days). However, T3 (GA3 300 ppm) showed best results with plant spread and T2 (GA3 250 ppm) with fresh and dry weight of flower (g) and diameter of flowers (cm).